Aktivitas Hepatoprotektif Ekstrak Kunyit (Curcuma domestica Val.) dan Ekstrak Meniran (Phyllantus niruri Linn.) Pada Tikus yang Diinduksi Parasetamol Kajian Histopatologi Liver - Novianto, Agil; Nurrochmad, Arief; Puspitasari, Ika (Jurnal Farmasi (Journal of Pharmacy), 2014)
Curcuma domestica and Phyllanthus niruri was two plants which has been shown to have an effect hepatoprotective. This research was conducted to determine mechanism study of hepatoprotective combination of Curcuma domestica and Phyllanthus niruri extract to animals induced by paracetamol. Animals devide into 8 groups in random order of 5 each rats. Normal groups were give aquadest, negative groups (Paracetamol) were give CMC Na 0,5 %, positive goups were give silimarin with dose 100 mg/kg, Curcuma domestica groups with a dose of 100 mg/kg, Phyllanthus niruri groups with 200 mg/kg BW as well as a combination of I-III with Curcuma domestica and Phyllanthus niruri extract comparison of each of 75: 50; 50: 100; and 25: 150 mg/kg in BW. Test preparations are given for 7 days. On day 7, all groups except normal induced with paracetamol single dose2.5 g/kg for peroral 30 minutes after administering the test preparations. Hepatoprotective activity were analyzed using liver histopathology. The results showed that the combination I can inhibited liver necrosis and gives better hepatoprotective activity comparable with single dose with optimal Curcuma domestica and Phyllanthus niruri extract dose of 75 and 50 mg/kg.